2010
DOI: 10.1159/000302203
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of α-Thalassemia in Adana, Turkey: A Single Center Study

Abstract: Background/Aim: α-Thalassemia (α-thal) is a widespread genetic disorder throughout the world caused primarily by reduced synthesis of the α-globin chains, and it has been found at a high incidence in Turkey. Our aim in this study was to determine the frequency and molecular properties of α-thal in Adana, Turkey. Material and Methods: A total of 3,000 individuals comprising premarital couples or patients with anemia were screened between 2007 and 2008. Hematological parameters were analyzed using an automatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
3
22
2
Order By: Relevance
“…The frequency of this mutation has been reported to be as high as 70.8 % in a study of 17 HbH patients from Kuweit [27]. Other studies conducted in Turkey reported its frequency as less than 10 % [7,[11][12][13]. Even the frequency of α PA-2 α was higher than that of α PA-1 α mutation in two of these Turkish studies [11,12].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The frequency of this mutation has been reported to be as high as 70.8 % in a study of 17 HbH patients from Kuweit [27]. Other studies conducted in Turkey reported its frequency as less than 10 % [7,[11][12][13]. Even the frequency of α PA-2 α was higher than that of α PA-1 α mutation in two of these Turkish studies [11,12].…”
Section: Resultsmentioning
confidence: 84%
“…--MED mutation seems to be specific to Mediterranean areas. It has been reported among the first three or four most frequent mutations in Mediterranean and Middle Eastern populations whereas it has not to been seen in Far Eastern populations [7,16,17,19,20,24,26].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This mutation was the second most commonly seen mutation in the studies by Curuk et al and Guvenc et al, whereas the third most commonly seen mutation in the study by Oner et al with allele frequencies of 9.55, 14.06 and 20 %, respectively [10][11][12]. In the study by Sutcu et al [13] it was reported as 27.77 %.…”
Section: Discussionmentioning
confidence: 95%
“…In a study on patients with alpha-thalassemia from Cukurova region by Curuk et al, it was shown that there was -a 3.7 mutation in 59.3 % of patients and allele frequency was 29.6 % [11]. Guvenc et al detected -a 3.7 deletion in 181 of 450 alleles from 225 patients with alpha-thalassemia and allele frequency was reported as 40.66 % [12]. In a study by Sutcu et al [13] in which distribution of alpha-thalassemia mutations was investigated at Isparta province, -a 3.7 allele frequency was 5.55 %.…”
Section: Discussionmentioning
confidence: 99%